Rabbinic study circles : aspects of Jewish learning in its Late Antique context - Hirshman, Marc G.; Satran, David; Reisler, Anita, 1987- (Mohr Siebeck, 2020)
"Tracing the development of rabbinic education from the first centuries of the Common Era in Palestine through the flowering of centers of learning centuries later in Babylonia, the contributors to this volume examine varied aspects of the educational ethos, the tension between oral tradition and literary practice, and the role of the rabbinic sage as pedagogical innovator and model"--P
Keywords: Jewish learning and scholarship -- History -- To 1500.; Jewish religious education -- History -- To 1500.; Education, Ancient.; Éducation antique.; Education, Ancient; Jewish learning and scholarship; Jewish religious education; To 1500; History